Online innovation and repurchase intentions in hotels: the mediating effect of customer experience - George Kofi Amoako; Joshua Kofi Doe; Emmanuel Kotey Neequaye (International Hospitality Review)
Purpose – This study investigates how customer experience mediates the relationship between online innovation and repurchase intention in the hotel industry in Ghana. Design/methodology/approach – Data was collected from 167 clients from a two-star hotel in Accra, the capital city of Ghana. Structural equation modelling was used to analyse the relationship between the variables. Findings – Results from the analysis indicate that online innovation positively leads to higher repurchase intentions and better customer experience, affirming that customer experience leads to repurchase intentions. Thus, while online innovation leads to repurchase intentions, the strength of this repurchase intention depends on customer experience. Therefore, customer experience mediates the relationship between online innovation and repurchase intention in the hotel industry. Research limitations/implications – This study addressed only the customer's point of view; future studies could investigate the subject from the managers and other stakeholders' point of view to get a holistic view. Also, the sample size could be improved, and the study could be conducted in other African countries for comparison purposes. Practical implications – The study shows that online innovation does not automatically lead to increased positive repurchase intention. Hotel managers must, therefore, enforce good customer experience for better profitability. Originality/value – As far as the researchers know, limited studies have been conducted into how customer experience mediates online innovation and repurchase intention in the hotel industry in Ghana using structural equation modelling. This makes this research unique in Ghana. This study makes an original contribution by measuring the real effect of innovation on repurchase intentions in the hotel industry in Ghana.